Permeation of Water Nanodroplets on Carbon Nanotubes Forests. (31st January 2017) - Jaques, Ygor M.; Galvao, Douglas S.
ABSTRACT: Fully atomistic molecular dynamics simulations were carried out to investigate how a liquid-like water droplet behaves when into contact with a nanopore formed by carbon nanotube arrays. We have considered different tube arrays, varying the spacing between them, as well as, different chemical functionalizations on the uncapped nanotubes. Our results show that simple functionalizations (for instance, hydrogen ones) allow tuning up the wetting surface properties increasing the permeation of liquid inside the nanopore. For functionalizations that increase the surface hydrophilicity, even when the pore size is significantly increased the droplet remains at the surface without tube permeation.